Urban water health: A conceptual framework and assessment system - He, Jing; Li, Yunyan; Su, Jiafu; Liao, Bo (Frontiers in Ecology and Evolution, 2023)
A quantitative evaluation of urban water health is crucial to the decision-making process for water management. Healthy water does not only encompass excellent water quality and a diverse ecology but also has other characteristics, such as the amount of water resources, supply-use-drainage issues, the flood and water cycle, etc. In this study, a theoretical framework and an indicator system of urban water health were proposed by integrating ecosystem health and water cycle health. Subsequently, given the time scale and the regional characteristics, an objective evaluation model was applied which combined the real-coded accelerated genetic algorithm (RAGA) method with the projection pursuit (PP) method to calculate the indicator weights and the thresholds for an urban water health index (UWHI). The standard thresholds for the UWHI were calculated as (0.04,0.87], (0.87,1.80], (1.80,2.73], (2.73,3.50], (3.50,4.01], corresponding to the categories of Sick, Unhealthy, Subhealthy, Healthy and Excellent, respectively. Using the city of Chongqing as a case study, the results showed an urban water health index increase from 1.796 to 2.668 from 2011–2020, and the health level improves from Unhealthy to Subhealthy, approaching Healthy. For each subsystem, the results indicated that the health status of water cycle is superior to that of water ecosystem. Finally, important factors that affect water health were identified by analyzing the changes in the indicators in detail. The results of this study revealed that the main weaknesses of Chongqing are serious soil erosion, large domestic water use, high water consumption rate and unsatisfactory water functional areas,and indicate key priorities in the pathway toward future water management.